Muslim dilemma: conviction or hobson's choice? - Banerjee, Sumanta (2004)
Let down by the Congress and other secular political parties, muslims have nowhere to go. Thus, the spectacle of large numbers of Muslims, especially the young, joining the BJP on the eve of the Lok Sabha polls is a signifier of the age-old nostrum. `If you can't lick them, join them.' - Reproduced.
Keywords: Muslims; Politics and government